Cognitive Conflict Integrated CRT Approach Analysis of Students' Conceptual Understanding Using E-Modules - Yulianda Yulianda; Fatni Mufit; Fuja Novitra (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyse students’ conceptual understanding and the needs for interactive teaching materials based on a cognitive conflict model integrated with a Culturally Responsive Teaching (CRT) approach. The research was conducted through a survey in three high schools in Padang City: SMAN 4, SMAN 9, and SMAN 11. A qualitative descriptive method was used, supported by a diagnostic test comprising 15 questions classified into four categories: conceptual understanding, lack of understanding, misconceptions, and not knowing the concept. The findings indicate that students’ average conceptual understanding remains below 50%. Significant misconceptions were identified in dynamics (41.82%), while high levels of conceptual ignorance were found in kinematics (51.91%). The needs analysis shows that teachers and students require interactive and culturally relevant materials to address these persistent misconceptions and support clearer conceptual construction. The results suggest that teaching materials incorporating cognitive conflict strategies can effectively challenge students’ initial ideas, while the CRT approach contextualises physics concepts within students’ cultural experiences. In conclusion, the development of interactive e-modules integrating cognitive conflict and CRT is needed to address conceptual difficulties and improve students’ understanding of fundamental physics concepts